DNA-free CRISPR/Cas9 genome editing system for oil palm protoplasts using multiple ribonucleoproteins (RNPs) complexes - Norfaezah, Jamaludin; Masani, Mat Yunus Abdul; Fizree, MD Piji Mohd Al-Akmarul; Bahariah, Bohari; Shaharuddin, Noor Azmi; Ho, Chai Ling; Rasid, Omar Abdul; Parveez, Ghulam Kadir Ahmad (Elsevier, 2024)
CRISPR/Cas9 is a powerful genome editing tool applicable to diverse plant species. However, the application of CRISPR/Cas9-ribonucleoproteins (RNPs) in oil palm (Elaeis guineensis) has not yet been reported. In this paper, the specificity, efficiency, and sensitivity of CRISPR/Cas9-RNPs in oil palm were evaluated by assessing the effect of different amounts of Cas9 and heat stress using E. guineensis phytoene desaturase (EgPDS) as the target gene. Seven gRNAs were designed and combined with Cas9 protein to form three combinations of RNPs complexes; RNP1/RNP2, RNP3/RNP4, and RNP5/RNP6/RNP7. Assessment of optimal amount of Cas9 and heat stress using RNP5/RNP6/RNP7 demonstrated that 40 µg of Cas9 and heat treatment at 39ºC increased the genome editing efficiency up to 95 in oil palm protoplasts. The use of both optimal conditions produced targeted mutations at frequencies of up to 63.6 in protoplasts transformed with RNP1/RNP2 and RNP3/RNP4 and up to 100 with RNP5/RNP6/RNP7 combinations. Multiple site mutagenesis at two to three target sites with fragment removal up to 179 bp, 69 bp, and 816 bp occurred at high frequencies producing editing efficiency and a Knockout Score (KO) of 100. Altogether, this study demonstrates a promising, highly efficient, and precise transgene-free CRISPR/Cas9-RNPs genome editing platform in oil palm that also holds enormous potential for application in other transformation-recalcitrant species. © 2023 Elsevier B.V.